Kingdom of Swaziland : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues paper assesses Swaziland's export diversification and quality. Swaziland's export structure has experienced sizable changes over the past 15 years. The share of textile exports has halved, and the expiration of trade benefits under Africa Growth Opportunity Act (AGOA) implies that the share of textile exports would decline further. Swaziland's exports are relatively diversified with good quality index compared with its peers. However, diversification and product quality have declined in recent years, while the expiration of the access to AGOA calls for enhanced efforts in this area. Improving education and training, strengthening institutional framework, and further developing the financial market will help improve export diversification and quality upgrading.